The french perfumer - Hampson, Amanda ([North Sydney, New South Wales] : Penguin Random House Australia, 2018)
Shorthand typist required by English speaker in the South of France. Live-in, full board plus salary commensurate with experience.'Iris Turner, an unworldly young Englishwoman, arrives in the French Riviera to take up a secretarial role for the mysterious Hammond Brooke. Living in a small, exclusive hotel among eccentric and unpredictable aristocrats and struggling to gain her employer's trust, she soon realises that nothing is as it seems.Initiated into the mysterious world of perfume, she finds herself entangled in a web of intrigue and deception. Gradually discovering the truth, she gains a new understanding of the meaning of love, loyalty and betrayal.
Keywords: Perfumes -- Fiction; France -- Fiction; Australian